PERSEPSI DOSEN DAN TENAGA KEPENDIDIKAN TENTANG PERAN INTERNAL AUDIT DALAM UPAYA MEWUJUDKAN GOOD UNIVERSITY GOVERNANCE DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Dewi Sundari, Rispantyo & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the perception of lecturers and educators staff about the importance of role internal audit to achieve Good University Governance and analyze the perception of lecturers and educators staff about the effects of internal audit performance of the Good University Governance. This type of research is a survei of the lectures and educators staff at the University of Slamet Riyadi Surakarta. Methods of data collection used questionnaires and documentation. The sampling technique used purposive sampling with a sample of 78 people. Data analysis techniques used multiple linear regression. The results showed that the internal audit performance has positive effect to achieve of good university governance at the University of Slamet Riyadi Surakarta. But not significantly. This shows that the performance of internal audit less influential but its role is very important in achieving good university governance at the University of Slamet Riyadi Surakarta.Keywords: perception, role of internal audit, internal audit performance, good university governance